Pemindahan negatif dalam karangan Bahasa Sepanyol oleh pelajar Melayu / Fatina Abu Bakar - Fatina, Abu Bakar (2016)
The research explores the negative transfer phenomenon from the Malay Language and the English Language in the writing of Malay students who are learning the Spanish Language. The focus of the research is to identify the differences in the negative transfer between Malay and English Language. The research employs mixed method approach where the researcher will use basic statistics to calculate the frequency of negative transfer and will provide the descriptive explanation of the negative transfer. The primary data comprises of 30 essays of Malay students who are learning Spanish Language level 1. The mistakes of the students in the essay writings will be categorized according to the types of mistakes adapted from Calvo Cortés (2005) and subsequently analyzed using the negative transfer classification type (Odlin 1989). In addition, the data from the questionnaire will be used to investigate the perception of students towards the usage of Malay and English Language in the learning of Spanish Language. The findings show that students make more negative transfer from English compared to Malay and the type of negative transfer that they do most is the verb. Besides that, student’s perception towards language that they use as a reference in Spanish class is also English. The outcome of the research is expected to capture the interest of Spanish Language Instructors towards language transfer phenomenon and can be used to improve the teaching and learning of the Spanish Language particularly in Malaysia.